Kesetaraan Laki-Laki dan Perempuan Dalam Konteks Menerima Keselamatan (Study Eksegesis Galatia 3:26-29) Relevansi Bagi Gereja Masa Kini - Murnika Sahputri Padang; Herdiana Boru Hombing; Erman S.Saragih; Haposan Silalahi; Bernhardt Siburian (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the equality of men and women in the context of receiving salvation based on Galatians 3:26-29 with relevance for today's church. The research method in writing this scientific work is a qualitative method, namely a descriptive approach. This method is used by the author to find useful materials in accordance with the research objectives. In this research, equality between men and women will be explored in the context of receiving salvation and its relevance for the church today. The result of the exegesis of Galatians 3:26-29 is how humans view the equality of men and women in the context of receiving salvation and its relevance for the church today. As is known, Christians always emphasize that humans, both men and women, have equality in receiving salvation through His Gospel or His Word, namely the Faith and Trust of His people. In this case, it also really depends on the theological interpretation of each church sect, because some sects may emphasize a personal relationship with God as the main way to receive salvation, while there are several church sects that emphasize the role of the church as a community of faith that facilitates spiritual growth and receiving the gift of salvation. Salvation (grace) from God is universal (general). God's action in Jesus Christ has effectively eliminated differences according to Gal. 3:26-29. The good news of salvation is that there is no longer such a thing as a select group, those who hope to receive the benefits of Jesus' Messiahship should be part of every believing people. Salvation in the context of Galatians 3 is through God's promises to His people who believe. Apart from that, the concept of salvation is a primary doctrine that becomes a dogmatic guide for God's church. The church must also see and emulate the equality of men and women in the context of receiving salvation. God emphasizes that all mankind should not do things that God does not want. He hopes that those who come with Him are those who truly believe in their faith. Salvation is given to humans as a form of His goodness to His people who believe through Faith and Actions that are always loyal to Him. Salvation is Grace, meaning that there is only one way to obtain salvation, namely through Jesus Christ. He said, “I am the way and the truth and the life. No one comes to the Father except through Me.” And if you belong to Christ, then you are also Abraham's descendants and have the right to receive God's promises (Gal. 3:29).